Analysis of the essential oil chemical profiles of two Orobanche species: O. laxissima Uhlich & Rätzel and O. ramosa L. - Majid Khalifeh; Azadeh Hamedi; Ardalan Pasdaran (Trends in Pharmaceutical Sciences)
The Orobanche genus (broomrapes) is well-known as an herbaceous parasitic plant with a long history in traditional Asian medicine and folklore foods. The volatile components of two Orobanche species, O. laxissima and O. ramosa (branched broomrape), from two different areas, East Azerbaijan and Fars provinces, were analyzed in this study using hydrodistillation extraction and gas chromatography-mass spectrometry (GC-MS). Essential oils from O. laxissima and O. ramosa aerial parts consisted of fourteen and eight compounds, respectively, which represented 97.15% and 99.8% of total oil compositions. O. laxissima essential oil contains carvacrol (53.35%), thymol (9.65%), and trans-caryophyllene (5.17%), while, as a substantial difference, O. ramosa essential oil mostly contains carvacrol (81.53%), α-terpinolene (4.57%), and trans-caryophyllene (3.6%). As a significant difference, O. laxissima essential oil includes a significant content of aliphatic hydrocarbons, including tricosane (5.46%), tetracosane (5.62%), and docosane (1.13%), whereas O. ramosa essential oil excludes these components. The monoterpene, and sesquiterpene profiles of both plants were similar, especially for α-terpinolene, spathulenol, and hotrienol. Although these essential oils contained similar phytochemical profiles, the differences may serve as marker references for future research on Orobanche species.